Primary resistance against integrase strand transfer inhibitors in integrase strand transfer inhibitor-naive patients failing first- and second-line ART in Tanzania. (14th September 2022) - Henerico, Shimba; Lyimo, Eric; Makubi, Abel N; Magesa, Daniel; Desderius, Bernard; Mueller, Andreas; Changalucha, John; Kalluvya, Samuel E; Van Zyl, Gert; Preiser, Wolfgang; Mshana, Stephen E; Kasang, Christa
Abstract: Introduction: Sub-Saharan African countries are introducing integrase strand transfer inhibitors (INSTIs) in their ART programmes as the preferred first-line regimen, and dolutegravir is the INSTI of choice due to its potency, tolerability and high genetic barrier to resistance. Dolutegravir was introduced into the first-line ART regimen in Tanzania in 2019. However, there is a paucity of data on the occurrence of mutations in HIV lineages circulating in Tanzania. This study aimed to determine the prevalence of INSTI primary resistance mutations in Tanzanian patients exposed to ART but not INSTIs. Methods: Plasma samples from 50 INSTI-naive patients failing first- or second-line ART [median (IQR) age: 40 (21.93–46.41) years; 68% women] were subjected to Sanger sequencing of the HIV integrase gene. Participants had been on ART for a median (IQR) duration of 7.32 (4.73–9.29) years, with 80% and 20% failing first- and second-line ART, respectively. Results: No major INSTI mutations were found, but 2 (4%) participants had the accessory mutation T97A. Using the REGA HIV-1 subtyping tool, HIV subtype A1 (53.1%) was found to be dominant, followed by subtypes C (30.6%) and D (16.3%). Conclusions: This study found no current evidence for transmitted resistance against INSTIs among unexposed patients failing ART and supports the scale-up of INSTI-based regimens. However, the presence of accessory mutations calls for the surveillance of INSTI resistance mutations to ensure that the anticipated long-term desired outcomes are achieved.